2020
DOI: 10.3389/fimmu.2020.572186
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Pathoetiology of Multiple Sclerosis: Has the Tail Been Wagging the Mouse?

Abstract: Multiple Sclerosis (MS) is traditionally considered an autoimmune-mediated demyelinating disease, the pathoetiology of which is unknown. However, the key question remains whether autoimmunity is the initiator of the disease (outside-in) or the consequence of a slow and as yet uncharacterized cytodegeneration (oligodendrocytosis), which leads to a subsequent immune response (inside-out). Experimental autoimmune encephalomyelitis has been used to model the later stages of MS during which the autoimmune involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 174 publications
(313 reference statements)
0
49
0
1
Order By: Relevance
“…Interestingly, Caprariello et al ( 2018 ) and Almuslehi et al ( 2020 ) showed that oligodendrocyte degeneration and microglial activation recruit adaptive immune cells (pan CD3 T-cells and CD8 T-cells) and trigger subsequent demyelination in cuprizone-fed mice once the blood-brain barrier is compromised (using pertussis toxin injection). Whether oligodendrocytes apoptosis and microglial activation (as shown in this study; Wu et al, 2020 ) attract adaptive immune cells (e.g., T-cells) into the CNS to facilitate subsequent adaptive immune cell-mediated oligodendrocyte degeneration (Stys et al, 2012 ; Sen et al, 2020b ; as in 'inside-out' theory of MS) remains unexplored.…”
Section: Potential Involvement Of Microglia and Astrocytes In The Myementioning
confidence: 74%
“…Interestingly, Caprariello et al ( 2018 ) and Almuslehi et al ( 2020 ) showed that oligodendrocyte degeneration and microglial activation recruit adaptive immune cells (pan CD3 T-cells and CD8 T-cells) and trigger subsequent demyelination in cuprizone-fed mice once the blood-brain barrier is compromised (using pertussis toxin injection). Whether oligodendrocytes apoptosis and microglial activation (as shown in this study; Wu et al, 2020 ) attract adaptive immune cells (e.g., T-cells) into the CNS to facilitate subsequent adaptive immune cell-mediated oligodendrocyte degeneration (Stys et al, 2012 ; Sen et al, 2020b ; as in 'inside-out' theory of MS) remains unexplored.…”
Section: Potential Involvement Of Microglia and Astrocytes In The Myementioning
confidence: 74%
“…Alternatively, MS can be considered as a primary degenerative condition that initiates the myelinating unit (oligodendroglia, their processes, and myelin) and results in neuroinflammation (the “inside-out” hypothesis) [ 81 ]. Researchers conducting a study on the cuprizone-induced demyelination in an animal model—enabling the study of oligodendrocytosis in the absence (immuno-suppression) and presence (immuno-protection) of the peripheral immune system—postulate that MS primarily originates from a slow, progressive oligodendrocyte degeneration caused by metabolic dysfunction that leads to subsequent reactive gliosis in the absence of adaptive immune cell response [ 82 ].…”
Section: Does Infection Of Sars-cov-2 May Be An Actual Neurodegenementioning
confidence: 99%
“…Although no animal models faithfully mimic the complete complexity of MS, the appropriate use of models depends upon the specific research question being posed [ 12 ]. Despite the differences in disease induction in EAE (peripheral injection of myelin protein) and CPZ (feeding of toxic compound), both experimental models show oligodendrocyte degeneration, demyelination, and glial activation in the CNS [ 14 , 224 ].…”
Section: Discrepancies Between Animal Models and Ms At The Proteome Levelmentioning
confidence: 99%
“…Moreover, in MS and EAE, proteins related to the adaptive immune responses (e.g., immunoglobulin and complement) were more common, whereas proteins of the innate immune response were identified in CPZ (e.g., glial fibrillary acidic protein, GFAP; Supplementary Figure S1c,d ). Due to these immunological similarities between EAE and MS, EAE has been widely considered as ‘the’ model of MS [ 12 , 225 ]. However, samples from MS patients were collected after clinical diagnosis or post-mortem [ 58 , 76 ].…”
Section: Discrepancies Between Animal Models and Ms At The Proteome Levelmentioning
confidence: 99%
See 1 more Smart Citation